Return of the hero [videorecording (DVD)] - Tirard, Laurent, 1967-; Tirard, Laurent, 1967-; Dujardin, Jean, 1972-; Laurent, Mélanie, 1983-; Merlant, Noémie, 1988- (Distrib Films collection., 2019)
In early nineteenth-century France, a captain returns home from war as a penniless deserter but is welcomed as a war hero, and when he assumes that role, he must battle wits with his fiancée's sister who knows the truth but impersonated him while he was gone by writing letters to her sister on his behalf.